Emotions as The Basis of Literary Representations - Irana Austiningsih (Universitas Merdeka Malang, 2016)
This article is based on the belief that elemental human motives and basic emotions provide the deep structure of literary representations, and this dep structure serves to organize the particularities of circumstances and individual indentity. Personal power and reproductive success are governing purposes in life and in literary representations. Literature and its antecedents organize experience in personally meaningful ways. They provide models of behavior and help regulate the complex cognitive machinery through which humans negotiate their school social and cultural environments. To support this analysis, a reading of a contemporary Australian writer Elizabeth Jolleys Palomino will be presented. Like of other works of the novelist, Palonimo depicts women, not Woman in the sense that female individual stands in relation to the others of the same sex. Here, one can be the multiple roles of a woman including the desires, the social struggle of the gender identity, and the basic instincts of makind. The symbolism and the literary technique used even supports the university of woman deciption in this novel.